Hepatocyte PRMT1 protects from alcohol induced liver injury by modulating oxidative stress responses - Jie Zhao (Nature Portfolio, 2019)
Abstract Protein Arginine methyltransferase 1 (PRMT1) is the main enzyme of cellular arginine methylation. Previously we found that PRMT1 activity in the liver is altered after alcohol exposure resulting in epigenetic changes. To determine the impact of these PRMT1 changes on the liver’s response to alcohol, we induced a hepatocyte specific PRMT1 knockout using AAV mediated Cre delivery in mice fed either alcohol or control Lieber-DeCarli liquid diet. We found that in alcohol fed mice, PRMT1 prevents oxidative stress and promotes hepatocyte survival. PRMT1 knockout in alcohol fed mice resulted in a dramatic increase in hepatocyte death, inflammation and fibrosis. Additionally, we found that alcohol promotes PRMT1 dephosphorylation at S297. Phosphorylation at this site is necessary for PRMT1-dependent protein arginine methylation. PRMT1 S297A, a dephosphorylation mimic of PRMT1 had reduced ability to promote gene expression of pro-inflammatory cytokines, pro-apoptotic genes BIM and TRAIL and expression of a suppressor of hepatocyte proliferation, Hnf4α. On the other hand, several functions of PRMT1 were phosphorylation-independent, including expression of oxidative stress response genes, Sod1, Sod2 and others. In vitro, both wild type and S297A PRMT1 protected hepatocytes from oxidative stress induced apoptosis, however S297D phosphorylation mimic PRMT1 promoted cell death. Taken together these data suggest that PRMT1 is an essential factor of liver adaptation to alcohol; alcohol-induced dephosphorylation shifts PRMT1 toward a less pro-inflammatory, more pro-proliferative and pro-survival form.